UTILIZATION OF SUJONO BEACH AS A NATURAL LABORATORY FOR IDENTIFICATION OF INVERTEBRATE ANIMALS IN BIOLOGY EDUCATION - Ramadhan, Aldiansyah; Ilma, Zizni; Tarigan, Lola Zeramenda (Universitas Negeri Medan, 2025)
This study aims to identify the diversity of invertebrate species in the Sujono Beach area, Lalang Village, Medang Deras District, Batubara Regency. The study, which was conducted on May 27, 2025, used direct observation and survey methods to collect specimens. The collected invertebrates were then identified taxonomically based on morphological, anatomical, physiological, and behavioral characteristics to the phylum, class, and order levels, followed by wet preservation. The results of the study showed significant invertebrate diversity, especially from the Mollusca and Arthropoda phyla. A total of 14 species of Mollusca were identified, including Anadara antiquata , Turritella communis , and Placuna placenta . In addition, 3 species of Arthropods were also found, namely Macrobrachium rosenbergii and Scylla spp. , and one species of Echinodermata, Tripneustes gratilla . The high invertebrate diversity indicates that the environmental conditions of Sujono Beach are relatively well maintained. This study underscores the potential of Sujono Beach as a natural laboratory for biology education, particularly in invertebrate identification, and highlights the importance of sustainable habitat management and conservation efforts to maintain ecological balance and ensure the long-term sustainability of this species.